Shiāghatu Manhaji Qism Ta’līm al-Lughah al-‘Arabiyyah bi Jāmi’ati Batu Sangkar al-Islāmiyyah al-Hukumiyyah wa ‘Alāqatihaa bi Manhaj al-Lughah al-‘Arabiyyah fī al-Madrasah al-Mutawasithah - Kamaluddin Kamaluddin; Ferki Ahmad Marlion; Muhammad Yusuf Salam; Yuri Choiratinnisa (University of Darussalam Gontor, 2022)
This research aims to describe how the approach to curriculum development of the Arabic language department at Batusankar State Islamic University, implementation of Arabic curricula in MTs / West Sumatra, relationship of the Arabic language curriculum of Batusankar State Islamic University with the achievement of the objectives of the Arabic curricula MTs / in West Sumatra. This research uses a qualitative design, with a multi-faceted approach to discuss the synchronization of the curricula of Arabic education departments with Arabic language teaching in MTs/ in West Sumatra and then obtaining this research data using documentation, observation and in-depth interview techniques. Then validate the data correctly, constraints by triangulating the data. The results showed that the curriculum of the Arabic language department at Batusankar State Islamic University is the result of